(3GdeeJY aj GdJUQjas - (3GHf YUahQ , Ydj Hf eDef Hf eMeO GdMVQej GdGTHjdj, CHh GdMSf,J (B669 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG QCjJ GdfMhjjf hVYJ ai Pdc cJGHG SejJg HGdeeJY djchf ESeg hab eYfGg s
(3BNQgG (B:s
(3jfJgi HGdMOjK Yf GdeSGFd GdeHfjI eeG dGjLhR GdJUQja ajg Hbhdg (B: (3eKd LGdjhfhS hgPg LedI ef GdeSGFd jOQi dHgG GdeJcde hdg ajgG ZfjI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdUQas